Military crimes - Wright, Jacob L.; Crouch, C.L. (Oxford University Press, 2015)
Concerned with Israel’s history and future, the Bible devotes considerable space to war—the most powerful catalyst of change in the lives of nations. The biblical authors often display a consciousness of illicit activities in wartime, anticipating what we would call today “war crimes” or “military crimes.” And they also produced the first known examples of written laws of war. While the so-called Code of Hammurabi from Mesopotamia contains stipulations for soldiers, it is concerned with methods of conscription, military discipline, and concerns of soldiers’ families—yet not conduct on the battlefield. Ancient cultures from the Aegean and Western Asia, however, do reflect a general sense of what one deemed to be “lawful” conduct for armies. In some places they even moved in the direction of formal law. Setting a precedent for later international law and war conventions, some ancient Greek city-states formed interstate leagues (“amphictyonies”) and took oaths that they would not destroy each other’s cities (and especially their municipal water sources). Similarly, in the fifth book of Plato’s Republic, Socrates argues for the necessity of a law sanctioning Hellenic armies that lay waste to arable land. In the Hebrew Bible, we find an even more deliberate effort to define and depict what actions are permissible and forbidden in wartime.